2022
DOI: 10.1007/s40120-022-00389-x
|View full text |Cite
|
Sign up to set email alerts
|

Autologous Hematopoietic Stem-Cell Transplantation in Multiple Sclerosis: A Systematic Review and Meta-Analysis

Abstract: Introduction:In 1995, the use of autologous hematopoietic stem-cell transplantation (AHSCT), which was previously used to treat hematological tumors, was introduced for severe autoimmune diseases such as multiple sclerosis (MS). AHSCT has proven its safety over the past few years due to technical advances and careful patient selection in transplant centers. While most studies have reported that AHSCT led to decreased Expanded Disability Status Scale (EDSS) scores, some patients reported increased EDSS scores f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 79 publications
1
11
0
Order By: Relevance
“…Randomised evaluations of aHSCT are lacking, and most information is from real-world analyses [ 87 ]. A recent meta-analysis (2022) showed that, compared with before treatment, aHSCT reduced the frequency of MS relapses, and MRI activity decreased disability (EDSS score), and promoted NEDA (68% of patients) [ 88 ]. Retrospective observational data suggest that aHSCT is effective in patients with insufficient response to previous IRT [ 89 ].…”
Section: A Note On Autologous Haematopoietic Stem Cell Transplantatio...mentioning
confidence: 99%
“…Randomised evaluations of aHSCT are lacking, and most information is from real-world analyses [ 87 ]. A recent meta-analysis (2022) showed that, compared with before treatment, aHSCT reduced the frequency of MS relapses, and MRI activity decreased disability (EDSS score), and promoted NEDA (68% of patients) [ 88 ]. Retrospective observational data suggest that aHSCT is effective in patients with insufficient response to previous IRT [ 89 ].…”
Section: A Note On Autologous Haematopoietic Stem Cell Transplantatio...mentioning
confidence: 99%
“…Several studies have reported the development of ADs as a complication of SARS-CoV-2 infection. Acute transverse myelitis, autoimmune encephalitis, acute necrotizing myelitis, and CNS vasculitis are among ADs COVID-19 complications (10)(11)(12)(13). Bonometti et al reported the first case of systemic lupus erythematosus (SLE) following COVID-19 infection (14).…”
Section: Does Any Relationship Exist Between Autoimmune Disease and D...mentioning
confidence: 99%
“…Second, high titer of IgG antineuronal autoantibodies in some cases (30), however, this observation seems to be controversial, since there were also reports of "antibody-negative" autoimmune encephalitis. Third, clinical resolution of symptoms after immunomodulatory treatments like steroid therapies (11).…”
Section: Autoimmune Encephalitismentioning
confidence: 99%
See 2 more Smart Citations